Women’s Leadership and Firm Performance: Family Versus Nonfamily Firms - Nekhili, Mehdi; Chakroun, Héla; Chtioui, Tawhid (2018)
We evaluate the relationship between the appointment of women to CEO or Chair positions and firm performance, and shed light on the differences between family and nonfamily firms. By using a propensity score matching approach on a sample of 394 French firms over the period 2001–2010, we find major discordances between women’s leadership style and family business expectations relative to firm performance, as measured by return on assets and Tobin’s q. Notably, our results support the conjecture that family firms, which are more conducive to transformational leadership, offer women a more appropriate climate for exercising the function of Chair than that of CEO. In contrast, women CEOs perform better in nonfamily firms. Our findings move away from the predominant focus on barriers and stereotypes images about the female leadership and support the contingency theory of leadership, which states that the effectiveness of a leadership style depends on the organization and culture in which leaders operate, and on task-related positions
Keywords: propensity score matching; Performance; Contingency theory of leadership; Transformational Leadership; Family firms; Woman leadership